2007
DOI: 10.4310/hha.2007.v9.n2.a16
|View full text |Cite
|
Sign up to set email alerts
|

Homotopy types of truncated projective resolutions

Abstract: We work over an arbitrary ring R. Given two truncated projective resolutions of equal length for the same module we consider their underlying chain complexes. We show they may be stabilized by projective modules to obtain a pair of complexes of the same homotopy type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…For finite groups it has been shown that the 'geometric' D (2) property is equivalent to the 'algebraic' realization property [1, theorem I]. Indeed in one direction this is extended to all finitely presented groups [1, appendix B]:…”
Section: W H Mannanmentioning
confidence: 99%
See 3 more Smart Citations
“…For finite groups it has been shown that the 'geometric' D (2) property is equivalent to the 'algebraic' realization property [1, theorem I]. Indeed in one direction this is extended to all finitely presented groups [1, appendix B]:…”
Section: W H Mannanmentioning
confidence: 99%
“…In 1965 Wall introduced the problem and showed that a counter example must have n 2(see [5]). The question of whether or not such a complex exists is known as 'Wall's D (2) problem'. So a counter example must be (up to homotopy equivalence) a finite 3-complex of cohomological dimension 2, which is not homotopy equivalent to any finite 2-complex.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2007, Mannan in [3] considered two truncated projective resolutions of equal length for the same module and obtained a pair of complexes of the same homotopy type. This paper generalizes projective resolutions to proper left C-resolutions and similar results are obtained, where C is a subcategory of R-modules.…”
Section: Introductionmentioning
confidence: 99%